Politics of hesitance and the formation of ethical subjects through responsible gambling practices - Selin, Jani (Frontiers in Sociology, 2022)
Instead of harm prevention and risk related to gambling products, responsible gambling discourse emphasizes the importance of voluntary measures. From the point of view of governmentality, the responsible gambling practices produce, rely on, and call forth subjectivities. The aim of the study is to find out what kind of subjects are being produced through the responsible gambling practices of four Nordic state-owned gambling companies. As the companies are state-owned and operate on different types of markets, there are reasons to suspect that the companies could endorse different versions of the figure of responsible gambler. Previous research indicates that responsible gambling practices typically presuppose or aim to produce a self-governing subject making informed choices. Less attention has been given to detailed analyses of the heterogeneous factors contributing to the ethical subject formation. Moreover, there is a growing body of literature indicating, that along with the use of detailed behavioral data (big data), new forms of governmentality, that are highly relevant from the point of view of subject formation, are emerging. The responsible gambling practices are analyzed along Michel Foucault´s four aspects of ethics. First, there is ethical substance, the problematic aspect of the self that is taken as the target of the ethical work. Second, the subject needs to have a certain relation to social norms and moral codes. Third, ethical work is needed to mold the problematic aspect of the self. Fourth, the aim of the ethical work is a certain mode of being or relationship to oneself. The analyzed material consists of the annual reports of the companies between 2019 and 2021. The results show that the figure of subject making informed voluntary choices is deeply embedded in the responsible gambling practices of the companies. The companies entice the gamblers to think about themselves and to act upon themselves as subjects capable of self-control. Hesitancy to intervene characterizes the activities of the companies, even if all the companies collect and use detailed behavioral data. The inclusion of the precarious subject of gambling harm would allow the companies to do much more to prevent gambling harm.